Natural compounds ursolic acid and digoxin exhibit inhibitory activities to cancer cells in RORγ-dependent and -independent manner - Zou, Hongye; Yang, Yatian; Chen, Hong-Wu (Frontiers in Pharmacology, 2023)
Natural compounds ursolic acid (UA) and digoxin isolated from fruits and other plants display potent anti-cancer effects in preclinical studies. UA and digoxin have been at clinical trials for treatment of different cancers including prostate cancer, pancreatic cancer and breast cancer. However, they displayed limited benefit to patients. Currently, a poor understanding of their direct targets and mechanisms of action (MOA) severely hinders their further development. We previously identified nuclear receptor RORγ as a novel therapeutic target for castration-resistant prostate cancer (CRPC) and triple-negative breast cancer (TNBC) and demonstrated that tumor cell RORγ directly activates gene programs such as androgen receptor (AR) signaling and cholesterol metabolism. Previous studies also demonstrated that UA and digoxin are potential RORγt antagonists in modulating the functions of immune cells such as Th17 cells. Here we showed that UA displays a strong activity in inhibition of RORγ-dependent transactivation function in cancer cells, while digoxin exhibits no effect at clinically relevant concentrations. In prostate cancer cells, UA down-regulates RORγ-stimulated AR expression and AR signaling, whereas digoxin up-regulates AR signaling pathway. In TNBC cells, UA but not digoxin alters RORγ-controlled gene programs of cell proliferation, apoptosis and cholesterol-biosynthesis. Together, our study reveals for the first-time that UA, but not digoxin, acts as a natural antagonist of RORγ in the cancer cells. Our finding that RORγ is a direct target of UA in cancer cells will help select patients with tumors that likely respond to UA treatment.